THE ISSUES OF SHARIA COMPLIANCE IN E-WALLET SERVICES AND PRODUCTS IN MALAYSIA: AN ANALYTICAL STUDY BASED ON MAQASID SHARIA (SALAM Digest: Syariah and Law Undergraduate Symposium, 2024)
E-wallet services and product is a component or program in an e-wallet application that provides various functions to its users. The importance of shariah compliance in e-wallet products and services is that it ensures that financial transactions adhere to Islamic ethical and legal principles, fostering trust and inclusivity among Muslim users. The use of this e-wallet began to be widely used when the world was attacked by the covid-19 epidemic because it can be transmitted through physical contact. So the use of e-wallet is highly demanded because it helps to reduce the physical reaction among people while also reducing the risk of being affected by the covid-19 epidemic. So the use of e-wallet, in order to protect the welfare of life and property in line with the concept of maqasid sharia. Maqasid shariah is a discipline of knowledge regarding the purposes and regulations set by God for each of his laws in order to protect the welfare of mankind. This research evaluates the definition and framework Shariah compliance of e-wallet services and products in Malaysia, categorizing them into compliant and non-compliant groups, and examines their alignment with Maqasid Shariah principles, particularly focusing on the preservation of property (Hifz Mal), to understand their impact and justification within Islamic financial ethics. Thus this research use a qualitative method and there are several methodology that had been applied such as library method and interview whether direct and indirect way. Therefore this study's significance lies in assessing the Shariah compliance of e-wallet services and products in Malaysia, enhancing understanding of their ethical role in Islamic finance.